Three-year follow-up case report: root canal treatment combined with intentional replantation for treating type III palatogingival groove in a maxillary lateral incisor - Jia, Jixu; Cheng, Miao; Shi, Sumeng; Qiao, Yanchun (Frontiers in Oral Health, 2025)
Palatogingival groove is a developmental anomaly that can lead to significant periodontal and periapical diseases, particularly in Type III, which extends to the apex and communicates with the periodontal membrane through the apical foramen. This case report details the management of a Type III palatogingival groove in a maxillary lateral incisor, combining root canal treatment and intentional replantation, followed by a 3-year follow-up to assess the mid-term efficacy of this approach. The patient presented with a narrow and deep periodontal pocket on the palatal side, destruction of the palatal root surface and labial bone plate, and a persistent sinus tract. Initial treatment involved controlling the intracanal infection using root canal treatment under a dental microscope. One week later, the tooth was extracted for ex vivo preparation, including apical retrofilling and segmented filling of the root surface groove, before replantation and stabilization with elastic fixation on the labial side. At the 2-month follow-up, the labial sinus tract had completely healed. The palatal area, which initially exhibited a probing depth of 10 mm, demonstrated an 8-mm gain in clinical attachment. Probing revealed no signs of bleeding or pus discharge. Radiographic examinations showed the disappearance of periapical radiolucency. Regular follow-ups at 12, 24, and 36 months indicated no discomfort, with radiographic evidence of new bone formation at the apex and gradual recovery of the periodontal membrane, achieving new periodontal attachment. This case demonstrates that root canal treatment combined with intentional replantation, with a focus on infection control, is an effective treatment method for managing Type III palatogingival groove in maxillary lateral incisors.